Dongola 2015-2016. Fieldwork, conservation and site management (University of Warsaw Press, 2025)
The Polish Center of Mediterranean Archaeology University of Warsaw mission to Old Dongola has been excavating the site for over 50 years. This volume is a second comprehensive report on fieldwork and conservation conducted in 2015–2016 by a team led by Włodzimierz Godlewski. The contributions report on the work of recent seasons and present in-depth studies on the site’s urban development, architecture and building techniques. The volume also includes results of the most recent specialized research on material brought to light during these and earlier campaigns. The discussed categories of find include inscriptions, ostraka, pottery, animal bones, and textiles.